Radical Cyclisation of α‐Halo Aluminium Acetals: A Mechanistic Study. Issue 14 (18th February 2016) - Bénéteau, Romain; Boussonnière, Anne; Rouaud, Jean‐Christophe; Lebreton, Jacques; Graton, Jérôme; Jacquemin, Denis; Sebban, Muriel; Oulyadi, Hassan; Hamdoun, Ghanem; Hancock, Amber N.; Schiesser, Carl H.; Dénès, Fabrice
Abstract: α‐Bromo aluminium acetals are suitable substrates for Ueno–Stork‐like radical cyclisations affording γ‐lactols and acid‐sensitive methylene‐γ‐lactols in high yields. The mechanistic study herein sets the scope and limitation of this reaction. The influence of the halide (or chalcogenide) atom X (X=Cl, Br, I, SPh, SePh) in the precursors α‐haloesters, as well as influence of the solvent and temperature was studied. The structure of the aluminium acetal intermediates resulting from the reduction of the corresponding α‐haloesters has been investigated by low‐temperature 13 C‐INEPT diffusion‐ordered NMR spectroscopy (DOSY) experiments and quantum calculations, providing new insights into the structures of these thermally labile intermediates. Oxygen‐bridged dimeric structures with a planar Al2 O2 ring are proposed for the least hindered aluminium acetals, while monomeric structures seem to prevail for the most hindered species. A comparison against the radical cyclisation of aluminium acetals derived from allyl and propargyl alcohols with the parent Ueno–Stork has been made at the BHandHLYP/6‐311++G(d, p) level of theory, highlighting mechanistic similarities and differences. Abstract : Radical cyclisation with aluminium aggregates ! The radical cyclisation of α‐halo aluminium acetals has been studied in detail. Both monomeric and dimeric structures were found for these thermally labile aluminium acetals using 13 C‐INEPT DOSY experiments at low temperature and computational methods. The radical cyclisation was compared against the parent Ueno–Stork cyclisation, highlighting similarities and differences between the two reactions.